2022
DOI: 10.3390/ma15041449
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Embedded Copper Mesh Based on Cracked Template for Highly Durability Transparent EMI Shielding Films

Abstract: Embedded copper mesh coatings with low sheet resistance and high transparency were formed using a low-cost Cu seed mesh obtained with a magnetron sputtering on a cracked template, and subsequent operations electroplating and embedding in a photocurable resin layer. The influence of the mesh size on the optoelectric characteristics and the electromagnetic shielding efficiency in a wide frequency range is considered. In optimizing the coating properties, a shielding efficiency of 49.38 dB at a frequency of 1 GHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…These unintended holes can trap silver ink during curing, thereby reducing transmission. Thus, there is a limitation on etching time, which depends on the thickness 57 ZnO/Ag/ZnO films, 28 ITO/Cu-doped/ITO films, 36 Cu mesh (Walia), 56 Cu mesh (Liao), 82 Ag mesh (Voronin), 58 Ag mesh (Kim), 65 Ag mesh (Lei), 46 Ag mesh (Li), 55 Cu mesh (Voronin), 59 Ag mesh (Chung), 51 and Ni mesh. of the template film.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unintended holes can trap silver ink during curing, thereby reducing transmission. Thus, there is a limitation on etching time, which depends on the thickness 57 ZnO/Ag/ZnO films, 28 ITO/Cu-doped/ITO films, 36 Cu mesh (Walia), 56 Cu mesh (Liao), 82 Ag mesh (Voronin), 58 Ag mesh (Kim), 65 Ag mesh (Lei), 46 Ag mesh (Li), 55 Cu mesh (Voronin), 59 Ag mesh (Chung), 51 and Ni mesh. of the template film.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In contrast, metal meshes tend to maintain consistent uniform properties without percolation or contact issues. Several well-established methodologies have been developed for the fabrication of metal meshes, including photolithography, , imprint lithography, 3D printing, , crack lithography, , electrodeposition, , e-beam direct writing, and self-assembly . Most of these methods, however, are costly, time-intensive, and often unsuitable for large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information regarding the comparison of our results with other The works from literature include Ag mesh (Zarei), [60] Ag/Cu mesh, [61] ZnO/Ag/ZnO, [31] ITO/Cu-doped/ITO, [30] Cu mesh (Walia), [62] Cu mesh (Liao), [63] Ag mesh (Voronin), [64] Ag mesh (Kim), [65] Ag mesh (Lei), [55] Ag mesh (Li), [50] and Cu mesh (Voronin). [66] studies works in literature can be found in Table S2 (Supporting Information).…”
Section: Single-layer Embedded Metal Meshes (Slemms)mentioning
confidence: 99%
“…In AgNW electrodes, the trade-off for increasing the electrical conductivity decreases the optical transmittance because they are uniformly coated over the entire area of the substrate. However, transparent electrodes with a metal-mesh structure may increase the electrical conductivity without reducing the optical transmittance by increasing the height of the electrode pattern while maintaining the line width and aperture size. Therefore, active research is underway on EM-shielding films with mesh-type transparent electrodes. Mesh-structured transparent electrodes can be broadly classified into a micromesh electrode (MME) or a nanomesh electrode (NME). The MME used in an EM-shielding film is mainly fabricated using methods such as electroplating, wet etching, and printing process. They are fabricated such that they have a line width in the range of 2–10 μm.…”
Section: Introductionmentioning
confidence: 99%